Interfaith Marriage Perspective of Positive Law and Islamic Law in Indonesia - Sujiman, Zubaidi (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2024)
This research study aims to explore and analyze interfaith marriages from the perspective of positive law and Islamic law. This research is included in the category of literature study research with the basis of the qualitative approach used. Data obtained through literature searches (secondary data) include primary legal materials, secondary legal materials, and tertiary legal materials. After the data was obtained, the next step was to test the validity of the data using a credibility test in the form of extending observations, increasing persistence and triangulation in the form of sources and techniques, and analyzing using qualitative descriptive analysis techniques. The results of the research show that juridically, interfaith marriages are still polemic due to the dualism of legal norms between the Marriage Law and the Population Administration Law so it has legal implications for the disparity of judges in determining requests for interfaith marriages. Meanwhile, interfaith marriages are not permitted according to Islamic law, so if they are still carried out, they will have negative consequences for the status of children born from an invalid marriage.